2018
DOI: 10.1002/cne.24477
|View full text |Cite
|
Sign up to set email alerts
|

The mechanosensory‐motor apparatus of antennae in the Oleander hawk moth (Daphnis nerii, Lepidoptera)

Abstract: Insect antennae are sensory organs of great importance because they can sense diverse environmental stimuli. In addition to serving as primary olfactory organs of insects, antennae also sense a wide variety of mechanosensory stimuli, ranging from low-frequency airflow or gravity cues to high-frequency antennal vibrations due to sound, flight or touch. The basal segments of the antennae house multiple types of mechanosensory structures that prominently include the sensory hair plates, or Böhm's bristles, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 73 publications
(125 reference statements)
1
24
0
Order By: Relevance
“…2a, d) consist of three main segments, the basal scapus and pedicellus as well as the long flagella with tens of annuli. The basal two segments carry important mechanosensory organs: Böhm’s bristles, a type of sensilla chaetica, are located in three distinct fields on the scapus (with ≈ 170 bristles each in the species Daphnis nerii ) and two fields with fewer bristles on the pedicellus (Sant and Sane 2018). Johnston’s organs are embedded within the cuticle, in the joint between scapus and pedicellus (Fig.…”
Section: Hawkmoth Sensesmentioning
confidence: 99%
See 1 more Smart Citation
“…2a, d) consist of three main segments, the basal scapus and pedicellus as well as the long flagella with tens of annuli. The basal two segments carry important mechanosensory organs: Böhm’s bristles, a type of sensilla chaetica, are located in three distinct fields on the scapus (with ≈ 170 bristles each in the species Daphnis nerii ) and two fields with fewer bristles on the pedicellus (Sant and Sane 2018). Johnston’s organs are embedded within the cuticle, in the joint between scapus and pedicellus (Fig.…”
Section: Hawkmoth Sensesmentioning
confidence: 99%
“…Johnston’s organs are embedded within the cuticle, in the joint between scapus and pedicellus (Fig. 2d), and are sensitive to fast passive antennal movements with low amplitudes (Sant and Sane 2018). Axons of sensory cells innervating these sensilla arborize in the antennal mechanosensory and motor centre in the deutocerebrum of the moths, close to the dendritic arborisations of antennal motor neurons (Kloppenburg et al 1997; Sant and Sane 2018).…”
Section: Hawkmoth Sensesmentioning
confidence: 99%
“…JO is composed of ca. 140 scolopidial sensory neurons, and senses passive vibrations in pedicel–flagellum joint 15 . Previous studies have shown that JO sense flagellar vibrations ranging from low-frequency vibrations due to airflow and gravity 2527 to high-frequency flight-related movements of the antennal base 2,27,28 .…”
Section: Resultsmentioning
confidence: 99%
“…Along with sensory inputs from the JO, the antennal motor system receives proprioceptive inputs from Böhm’s bristles 14,15 . Antennal movement stimulates neurons underlying these sensory hairs, in turn activating antennal motor neurons and associated muscles with latencies of ~10 ms 14 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation